(untitled) (CHORNOMORSKI BOTANICAL JOURNAL, 2015)
Plant community ordination by means of multidimensional scaling has been carried out to reveal optimum ways of preliminary transformation of data and the similarity/dissimilarity mesure, to identify multidimensional dimantions in terms of edafic properties and phytoindicator scales and to reveal character of interrelations of matrixes of plant community, phytoindicator scales and edafic properties. The received results testify that edafic and climatic scales matrixes bear the complementary information on edaphotop properties and possibly climatop. Most possibly that climatic scales at large-scale level bear the specific information on properties of environment. It is difficult to confirm, whether character of this information to adequate nominative properties of a scale at macrolevel is. But with confidence it is possible to say that climatic phytoindicator scales allow to differentiate ecological conditions in biogeocoenosis at large-scale level. Thus, at the given stage we tend to phenomenological interpretation of value of climatic phytoindicator scales at large-scale level.